The Relationship Between Emotion Regulation & Problem Solving in Dating Violence among Victims of Child Abuse - Elvandari, Meitria Allisa; Astuti, Rr. Dwi (Golden Ratio of Social Science and Education, 2025)
CATAHU data reveals an increase in dating violence cases in Indonesia. Multiple factors can influence dating violence. This study aims to determine the relationship between dating violence and problem-solving and emotional regulation in individuals who have experienced child abuse. The method used in this study was quantitative. Subjects were recruited through a questionnaire. A correlational design with a purposive sampling technique, involving 234 respondents who were victims of child abuse and had experienced dating violence. Data were collected through an online questionnaire using three Likert scales: the Dating Violence Scale (24 items, α = 0.938), the Emotion Regulation Scale (30 items, α = 0.945), and the Problem Solving Scale (22 items, α = 0.937). After statistical assumption testing and outlier elimination, the analysis was conducted on 33 respondents. The results showed no significant relationship between emotion regulation and problem solving with dating violence in child abuse victims, with p = 0.251 (null hypothesis rejectedThe minor hypothesis test showed no significant relationship between emotional regulation and dating violence (r = 0.279, p = 0.058) and between problem solving and dating violence (r = 0.285, p = 0.068). These findings indicate that dating violence in child abuse victims is more influenced by other complex factors such as childhood trauma, learning violent behavior, and psychosocial factors. This study contributes to the understanding that interventions to prevent dating violence in vulnerable populations require a holistic approach that considers various risk and protective factors comprehensively, rather than only focusing on improving emotional regulation and problem-solving skills alone. Furthermore, examining other factors, such as self-disclosure and help-seeking behavior, is recommended.